VD_FINDINFO HC / 2025 / 875 vom 12. November 2025 - VD Tribunal cantonal (2025)
CONTRAT DE TRAVAIL, RÉSILIATION ABUSIVE, PROTECTION DE LA PERSONNALITÉ | 328 al. 1 CO, 336 al. 1 let. a CO, 55 al. 1 CPC (CH)